Adapting the MgO-CO2 working pair for thermochemical energy storage by doping with salts. (1st April 2019) - Shkatulov, A.I.; Kim, S.T.; Miura, H.; Kato, Y.; Aristov, Yu.I.
Highlights: MgO doped with lithium-potassium nitrate is studied as a thermochemical material. Its carbonation/decarbonation kinetics as well as cyclic stability are investigated. The material shows a high energy storage density of 1.6 GJ/m 3 . The concept of chemical heat pump utilizing the MgO-CO2 pair is discussed. Abstract: In this work, the MgO-CO2 working pair has been adapted for thermochemical energy storage (TCES) at medium temperatures by the MgO modification with inorganic salts to promote the TCES dynamics. Brief screening of modifying salts showed that lithium acetate (LiOAc) and mixed lithium-potassium nitrate (Li0.42 K0.58 NO3 ) additives could considerably promote the MgO carbonation at P(CO2 ) ≤10 bar and T ≥300 °C. The de- and re-carbonation kinetics, as well as cycling stability of the doped MgO/MgCO3, was reported to outline possible TCES operating conditions (T = 280 °C–380 °C, P(CO2 ) = 0–1 bar). The heat storage capacity of the salt-promoted MgO was estimated to be 1.6 GJ/m 3 . A concept of chemical heat pump utilizing the MgO-CO2 working pair was discussed. The salt-promoted MgO-CO2 working pair was concluded to be promising for TCES.